Microneurographic portrait of 19 patients with small fiber neuropathy—A pilot study - Beisswanger, Andrea; Peschke, Greta Z.; Braak, Noortje W.M.V.D.; Dumke, Christina; Fiebig, Andrea; Espenkott, Volker; Lischka, Annette; Lampert, Angelika; Rolke, Roman; Dohrn, Maike F.; Namer, Barbara (Pain, 2025)
Small fiber neuropathy (SFN) is defined by dysfunction or degeneration of Ad and C fibers, causing impaired temperature perception and spontaneous neuropathic pain. We performed microneurography (MNG) to analyze C-nociceptor properties in 19 patients with SFN. C-nociceptors were classified as mechanosensitive or mechano-insensitive, and either “normal,” “hyperactive,” or “hypoactive.” Results were compared with quantitative sensory testing (QST), intraepidermal nerve fiber densities (IENFD), and ratings of ongoing spontaneous pain (OSP) and electrical sinusoidal stimulation (eSS). In 17 patients with SFN experiencing OSP, we observed pathological nociceptors. We found a significantly greater proportion of hyperactive nociceptors whenever OSP was present in the examined area—on the foot—(OSPF); however, on an individual level, there was no significant correlation between the rating of OSP and the proportion of hyperactive fibers. Pain ratings of eSS were higher in the OSPF group and correlated with the proportion of hyperactive nerve fibers in MNG. In conclusion, spontaneous activity and mechanically sensitized C-nociceptors, predominantly mechano-insensitive C fibers (CMi), are potential biomarkers for ongoing pain. As CMi functionality is not assessed via IENFD or QST, but correlated with OSPF and ratings of eSS, those measures might become valuable tools to characterize SFN because they assess nociceptor pathology relevant for spontaneous ongoing pain in SFN. Microneurography reveals C-nociceptor dysfunction beyond conventional testing such as QST or IENFD. Microneurography and rating of electrical sinusoidal stimuli may aid in diagnosing C-nociceptor dysfunction in cases with unaltered QST and IENFD and offer insights into the role of hyperactive C-nociceptors in ongoing neuropathic pain.
CRIS-Team Scopus Importer:2025-06-06
Keywords: Microneurography; Neuropathic pain; Nociceptor physiology; Small fiber neuropathy